Dialog in Anton Trstenjak kot njegov glasnik = About Dialogue and Anton Trstenjak as Its Messenger - Ramovš, Jože (Edinost in dialog, 2023)
The article is based on the need to improve interpersonal coexistence and cooperation in the family, work and society, and to improve communication. Dialogue is the essence of quality communication in words, behaviour and actions. The article breaks down its basic components: human awareness, the fundamental need to connect and the capacity to communicate. The article briefly discusses the methodology for developing a dialogic relationship and considers what a person can do when dialogue and coexistence tragically fall apart. This is followed by an overview of the work of Anton Trstenjak in terms of dialogue and coexistence, revealing several components and conditions for dialogue. His most known book Among People has five topical chapters: two on relations between generations, two on relations between the sexes and one on relations between neighbours.